2003
DOI: 10.1002/jssc.200301560
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin derivatives in enantiomer GC separation of volatiles. Part XXI: Complexation of some terpenoids with 2‐O‐acetyl‐3‐O‐methyl‐ and 2‐O‐methyl‐3‐O‐acetyl‐6‐O‐t‐hexyldimethylsilyl‐γ‐cyclodextrins: Molecular Mechanics and Molecular Dynamics

Abstract: Molecular Mechanics and Molecular Dynamics calculations were performed to simulate the 1 : 1 complex formation of 2-O-acetyl-3-O-methyl-and 2-O-methyl-3-O-acetyl-6-O-t-hexyldimethylsilyl-c-cyclodextrins with a group of monoterpenoids having the p-menthane skeleton (menthol, i-menthol, neo-menthol, neo-i-menthol, menthone, i-menthone, and 3-oxo-1,8-cineole) using nitrogen as simulated gas carrier. 1 : 1 complexes of the terpenoids studied are stable and non-bonded van der Waals interactions are mainly responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Cyclodextrin derivatives endowed with silyl/alkanoyl or alkyl/alkanoyl derivatizing groups represent popular chiral auxiliaries for gas chromatographic applications in the area of the enantiodiscrimination of chiral substrates lacking in hydrogen bond donor groups, which constitute challenging systems for the majority of the enantioseparation methods [ 19 , 20 , 21 ]. As an example, the gas chromatographic separation of the two enantiomers of 1,1,1,3,3-pentafluoro-2-(fluoromethoxy)-3-methoxypropane (compound B), a chiral degradation product of the fluorinated anesthetic sevoflurane [ 22 ], was achieved with high efficiency by selecting heptakis(2,3-di- O -acetyl-6- O - tert -butyldimethylsilyl)-β-cyclodextrin (AcSiCD7) as the chiral agent [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclodextrin derivatives endowed with silyl/alkanoyl or alkyl/alkanoyl derivatizing groups represent popular chiral auxiliaries for gas chromatographic applications in the area of the enantiodiscrimination of chiral substrates lacking in hydrogen bond donor groups, which constitute challenging systems for the majority of the enantioseparation methods [ 19 , 20 , 21 ]. As an example, the gas chromatographic separation of the two enantiomers of 1,1,1,3,3-pentafluoro-2-(fluoromethoxy)-3-methoxypropane (compound B), a chiral degradation product of the fluorinated anesthetic sevoflurane [ 22 ], was achieved with high efficiency by selecting heptakis(2,3-di- O -acetyl-6- O - tert -butyldimethylsilyl)-β-cyclodextrin (AcSiCD7) as the chiral agent [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both menthol and menthol-substituted ILs have been the subject of several studies employing computational chemistry methods—either molecular dynamics (MD) or quantum chemistry [ 7 13 ]. However, to the authors’ best knowledge, none of the earlier works has developed a force field designed and validated specifically for the menthol molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Bicchi et al [8,9] demonstrated the highest enantioselectivity in GC separation for octakis(2-O-methyl-3-O-acetyl-6-O-tert-hexyldimethylsilyl)-c-CD in comparison with octakis(2-Oacetyl-3-O-methyl-6-O-tert-hexyldimethylsilyl)-c-CD, octakis(2,3-di-O-acetyl-6-O-tert-hexyldimethylsilyl)-c-CD and octakis(2,3-di-O-methyl-6-O-tert-hexyldimethylsilyl)-c-CD. Busby and Vigh [10] have successfully used the sodium salt of heptakis(2-O-methyl-3-O-acetyl-6-O-sulpho)-b-CD for capillary electrophoretic enantioseparation.…”
Section: Introductionmentioning
confidence: 99%